Learning English Language in Nepal in the Narrative of Kewat Learners - Kappar, Hiralal; Bhatt, Surendra Prasad (NELTA Bagmati Journal, 2022)
Learning a second language seems problematic especially for those who have to learn one additional language except their mother tongue as a bridge in order to reach over the target one. With this mindset, this paper was written with the purpose of exploring the problems of learning English language along the Kewat learners of English in general and their accent problems in particular. For this, the notion of narrative approach was employed for collecting the stories of four Kewat learners of English language from the Mahottari district as data. From the stories, three major themes viz Learning Experience of Kewat and Accent Problem in Learning English were generated under the lens of cognitive theory of language learning where Narrative Inquiry is taken as a methodological standpoint. Finally, the conclusion indicated that the learners of Kewat community have many difficulties in learning the English language especially the accent related difficulties in which they have been facing the problem of uttering the English sounds like: /l/, /r/, /t∫/, and /∫/ because of their mother tongue interference based on Krashen theory of learning second language (1982).